Positioning Radio Dangdut Modern - Rizka Harahap; Anne Ratnasari (Bandung Conference Series: Public Relations, 2023)
Abstract. Radio Cosmo FM is one of the radio broadcasting genre dangdut in Bandung. Radio Cosmo FM performs positioning as a modern and leading dangdut radio with a segmentation of young people who are distinguishing from other dangdut radios. It aims to be a reservoir of music development especially in dangdut genres. Visual radio as today’s radio is also a supporter of such radio as dangdut radio. The aim of this study is to find out how the positioning strategies carried out by the company in terms of image differentiation, product diferenciation, listener segmentation, and Radio Cosmo Visual are attracting listeners. Data collection techniques by conducting observations and in-depth interviews with public relations marketing and broadcasters. The results of this study differentiate the music program carried out by Radio Cosmo as a modern dangdut radio, the leading has quite a lot of differentiation done to get the market share sought in terms of the presentation of music program that uses hits maker, the program of the event that became the foundation in delivering Radio cosmo as the modern radio dangdut by providing up-to-date information, the style of its broadcasters with a young boy style and Radio Cosmos Visual as an icon of modern change in the terms of media. The image displayed by Radio Cosmo is a modern radio broadcast but remains on its sidelines by implanting Islamic and cultural values with the segmentation of young people. This makes the positioning of the radio retains its image and expression in the midst of competitors because although Radio Cosmo is not a radio that is superior in all respects but Radio Cosme has a differentiator from other Radio that is the main line of listeners to keep listening to Radio Cosmos not only once but repeatedly. Abstrak. Radio cosmo FM merupakan salah satu radio yang menyiarkan genre dangdut di Bandung. Radio Cosmo FM melakukan positioning sebagai radio dangdut modern dan terkemuka dengan segmentasi anak muda yang menjadi pembeda dengan radio dangdut lain. Memiliki tujuan untuk menjadi wadah pengembangan musik khususnya pada genre dangdut. Radio visual sebagai radio masa kini juga merupakan pendukung radio tersebut sebagai radio dangdut yang kekinian. Tujuan dari penelitian ini untuk mengetahui bagaimana strategi positioning yang dilakukan perusahaan dari segi diferensiasi citra, diferensiasi produk, segmentasi pendengar, dan Radio Cosmo Visual yang menjadi daya tarik pendengar. Teknik pengumpulan data dengan melakukan observasi dan wawancara mendalam dengan marketing public relation dan penyiar. Hasil penelitian ini diferensiasi program musik yang dilakukan oleh Radio Cosmo sebagai radio dangdut modern, terkemuka memiliki cukup banyak diferensiasi yang dilakukan untuk mendapatkan pangsa pasar yang dicari dari segi penyajian program musik yang menggunakan hits maker, program acara yang menjadi andalan dalam menyampaikan Radio Cosmo sebagai radio dangdut modern dengan memberikan informasi terkini, gaya para penyiarnya dengan gaya anak muda dan Radio Cosmo Visual sebagai ikon perubahan modern dari segi media. Citra yang ditampilkan Radio Cosmo sebagai radio dangdut modern tetapi tetap pada kaidahnya dengan menanamkan nilai-nilai keislamaan dan budaya dengan segmentasi anak muda. Hal tersebut menjadikan positioning radio tersebut mepertahankan citra dan ekesitensinya ditengah competitor karena walaupun Radio Cosmo bukan merupakan radio yang unggul dalam segala hal tetapi Radio Cosmo memiliki pembeda dari Radio lain yang menjadi garis besar pendengar untuk terus mendengarkan Radio Cosmo tidak hanya sekali tetapi secara berulang.